Effect of exogenous progesterone and gonadotropin-releasing hormone application on maintenance of pregnancy in early pregnant ewes after prostaglandin f2 alpha injection - Mehmet Köse; Mehmet Salih Kaya; Mehmet Osman Atlı (Eurasian Journal of Veterinary Sciences)
Aim: We tested the hypothesis that exogenous progesterone (P4) and gonadotropin-releasing hormone applications (GnRH) would prevent detrimental effect of prostaglandinF2alfa (PGF2α) on early pregnancy in ewes by sustaining high plasma progesterone level. Materials and Methods: For this purpose, nine pregnant ewes (mating=0) were divided into 2 groups on day 18 as follows: (1) PGF2α group (125 mcg of d-cloprostenol injection on day 18, n=5); (2) PGF2α + P4 + GnRH group (125 mcg of d-cloprostenol injection on day 18 + 20 mg flugestone acetate (P4) for 7 days + 10 mg of buserelin acetate injection, on day 22, n=4). P4 was withdrawn on day 25. P4 concentration was measured on days 18 and 19 by ECLIA. Pregnancies were examined by using transrectal ultrasonography on days 18, 22, 25, and 35. Statistical difference between groups was analysed by chi-squared test. Results: P4 concentration declined to below 1 ng/mL on day 19 in both groups. While all pregnancies were terminated in PGF2α group by day 25, P4 prevented pregnancy loss in PGF2α + P4 + GnRH group (P<0.02). When P4 was withdrawn on day 25, half of pregnancies continued after GnRH in PGF2α + P4 + GnRH group until birth. Conclusions: Results suggest that exogenous P4 application is sufficient for maintaining early pregnancy in ewes, even if the corpus luteum (CL) is regressed. Furthermore, GnRH application on day 22 might luteinize dominant follicles and could be sufficient to maintain pregnancy after P4 is removed.